Aminomethylenehelicene Oligomers Possessing Flexible Two‐Atom Linker Form a Stimuli‐Responsive Double‐Helix in Solution. Issue 7 (18th May 2014) - Shigeno, Masanori; Sato, Masahiko; Kushida, Yo; Yamaguchi, Masahiko
Abstract Aminomethylenehelicene oligomers up to the (M)‐heptamer were synthesized by reductive amination from a formylhelicene building block. The oligomers containing more than three helicenes formed a double helix in 1, 3‐dilfuorobenzene. The (M)‐tetramer and (M)‐pentamer unfolded into a random coil by heating to 60 °C, whereas the (M)‐hexamer only slightly unfolded at the same temperature. A two‐sided thermal hysteresis was detected in the structural change of the (M)‐tetramer and (M)‐pentamer during cooling and heating. The (M)‐pentamer and (M)‐hexamer unfolded with the addition of trifluoroacetic acid and regenerated a double helix with the addition of triethylamine.